2020
DOI: 10.7150/jca.41123
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of age related genes in patients with lower grade glioma

Abstract: Objective: To analyze the prognostic effects of age in different tumor types and determine the prognostic significance of age related genes in patients with lower grade glioma (LGG). Methods: The relationships between age and tumor overall survival were determined by Kaplan-Meier survival analysis using The Cancer Genome Atlas (TCGA) dataset. The age related genes were identified using TCGA RNA-seq data. Univariate and multivariate cox regression were used to determine the prognostic significance of age relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 44 publications
4
16
0
Order By: Relevance
“…Epithelial membrane protein 3(EMP3) is considered to be a tumor suppressor, but this article found that this gene is a prognostic risk gene for LGG. Similar to our results, Haiwei Wang et al also found that EMP3 was associated with the worse prognosis of LGG patients [23] and Xiao-Xia Guo et al discovered EMP3 was also a risk gene in the process of developing a prognostic 4-gene panel for glioblastoma patients [24]. WEE1 G2 checkpoint kinase(WEE1) is reported to be an oncogenic nuclear kinase and a regulator of the G2 checkpoint.…”
Section: Discussionsupporting
confidence: 90%
“…Epithelial membrane protein 3(EMP3) is considered to be a tumor suppressor, but this article found that this gene is a prognostic risk gene for LGG. Similar to our results, Haiwei Wang et al also found that EMP3 was associated with the worse prognosis of LGG patients [23] and Xiao-Xia Guo et al discovered EMP3 was also a risk gene in the process of developing a prognostic 4-gene panel for glioblastoma patients [24]. WEE1 G2 checkpoint kinase(WEE1) is reported to be an oncogenic nuclear kinase and a regulator of the G2 checkpoint.…”
Section: Discussionsupporting
confidence: 90%
“…SERPINE1 was reported to be up-regulated in STAD tissues compared with normal tissues, and the overexpression of SERPINE1 was closely associated with worse prognosis among STAD patients [ 32 ]. In addition, SERPINE1 was reported to have excellent prognostic value among patients with lower grade glioma [ 33 ]. SERPINE1 was observed to be up-regulated in glioma tissues using immunohistochemistry, and high expression of SERPINE1 was associated with reduced DFS and OS in glioma patients [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…This conclusion was also proved by our study (AUC = 0:827 vs. 0.747 for lncRNA alone model and 0.739 for mRNA alone model; C-index = 0:812 vs. 0.702 for lncRNA alone model and 0.737 for mRNA alone model). Furthermore, the poor prognosis of LGG was traditionally determined according to clinical characteristics, including older age [23] and IDH1 nonmutational status [24,25]. Thus, whether the risk score was superior or added additional prognostic value to these current clinical systems for prognosis prediction was also an important focus in the signature studies [10,22,26].…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of PON2 led to a significant increase in tumor cell proliferation and resistance to oxidative stress [34], while silencing of PON2 expression inhibited cancer cell proliferation, migration, and invasion [24]. Patients with high PON2 expression had shorter OS compared with those having low PON2 expression [23]. These findings indicated that high expression of PON2 may represent a protective stress response.…”
mentioning
confidence: 95%